The project of the compact media-accelerator for the two-stream superheterodyne free electron laser - Kulish, Viktor; Lysenko, Olexandr; Gubanov, Igor; Vаldenmayer, Georgy (Proceedings of National Aviation University (archive), 2007)
The results concerning the project of compact two-stream superheterodyne free electron lasers, which can be constructed on the basis of MLIA-accelerator, are represented. In the work is described the nonlinear theory of the multi-harmonic TSFELs and accomplished corresponding physical and project analysis. A specific characteristic of the considered system is the source of intensive relativistic electron beam is constructed on the basis of a two-beam MLIA-accelerator. The design-scheme of the compact MLIA-accelerator is proposed and analyzed. It is shown that main merit of studied devices is their potential compactness.